Knowledge and awareness among female patients attending cardiac outpatient department in a super speciality hospital - Sharma, Sushil Kumar; Sawhney, Vineeta (International Journal of Research in Medical Sciences, 2017)
Background: Cardiovascular disease is the leading cause of mortality not only in males but also in females and knowledge about the disease is poor among them. Objective of the study was to assess the knowledge and awareness among female cardiac patients. Methods: This cross-sectional study was conducted in outpatient department of cardiology in a super specialty hospital of government medical college Jammu, Jammu and Kashmir, for a period of three month from 1st March to 31st May 2017. Female patients were given a questionnaire regarding socio demographic profile, knowledge and awareness were recorded and analyzed in percentage. Results: There were 216 female patients, out of which 56.9% were in age group of 41-60 years, 86.1% were housewives, 87.5% were married, 54.1% having education up to 10th standard and maximum were living in joint family and 52.7% having monthly family income above 20,000. 44.4% were suffering from hypertension. Maximum females 59.7% consider themselves as bulky, 83% have changed their eating habits, 66.6% have started work out after the onset of disease, 61%-62% were having awareness about the cardiac symptoms and 97.2% were following allopathic drug therapy. Conclusions: Overall knowledge and awareness about disease and risk factors among these females was good as these patients were already diagnosed patients and were coming for follow up. There is need of educational programme by involving primary health care workers and utilization of CVD guidelines as a better preventive strategy.